BAITUL MAAL WAT TAMWIL LEGALITAS DAN PENGAWASANNYA - Thalis Noor Cahyadi (JESI (Jurnal Ekonomi Syariah Indonesia), 2012)
Abstract As one of the non-bank sharia financial institution, BMT has grown rapidly in Indonesia. But the condition has not been supported by legality of BMT clearly. Until now, there is no regulation for BMT both inform a law and rules under the law, which states directly to existence of BMT. Some experts stated that BMT is same as cooperation in order to BMT subjects to the Law of Cooperation but other experts stated that BMT ran like a bank, so that it can not subjects to the law of cooperation, but must be a bank agrees with the banking laws. The problem is one of many problems founded. Another problem is watching and controlling problems. This paper will discuss about the legality and controlling of BMT. Keywords: BMT, legality, controlling.